5′ splice site GC>GT and GT>GC variants differ markedly in terms of their functionality and pathogenicity. Issue 8 (12th May 2020) - Lin, Jin‐Huan; Masson, Emmanuelle; Boulling, Arnaud; Hayden, Matthew; Cooper, David N.; Férec, Claude; Liao, Zhuan; Chen, Jian‐Min
Abstract: In the human genome, most 5′ splice sites (~99%) employ the canonical GT dinucleotide whereas a small minority (~1%) use the noncanonical GC dinucleotide. The functionality and pathogenicity of 5′ splice site GT>GC (+2T>C) variants have been extensively studied but we know very little about 5′ splice site GC>GT (+2C>T) variants. Herein, we have addressed this deficiency by performing a meta‐analysis of reported +2C>T "pathogenic" variants together with a functional analysis of engineered +2C>T substitutions using a cell culture‐based full‐length gene splicing assay. Our results establish proof of concept that +2C>T variants are qualitatively different from +2T>C variants in terms of their functionality and suggest that, in sharp contrast to +2T>C variants, most if not all +2C>T variants have no pathological relevance. Our findings have important implications for interpreting the clinical relevance of +2C>T variants and understanding the evolutionary switching between GT and GC 5′ splice sites in mammalian genomes. Abstract : To date, we know well the functionality and pathogenicity of 5' splice site GT>GC (+2T>C) variants but very little about those of 5' splice site GC>GT (+2C>T) variants. Herein, we performed a meta‐analysis of reported +2C>T "pathogenic" variants together with a functional analysis of engineered +2C>T substitutions. Our analyses establish proof of concept that +2C>T variants are qualitatively different from +2T>C variants in terms of their functionality and pathogenicity.